1994
DOI: 10.1007/bf00191429
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of inflammatory cytokines in human glomerulonephritis

Abstract: We evaluated the expression of inflammatory cytokines in renal tissues obtained from 45 patients with several types of glomerulonephritis. Immunofluorescence studies with specific antibodies to interleukin (IL)-1 alpha, IL-1 beta, IL-6, tumour necrosis factor (TNF)-alpha, and TNF-beta showed intense cytoplasmic staining in the glomeruli and interstitium. Cells positive for these cytokines were found frequently in tissue from patients with lupus nephritis (WHO Class IV) and membranoproliferative glomerulonephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
99
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 16 publications
8
99
1
2
Order By: Relevance
“…Renal tubule cells are competent to produce proinflammatory cytokines and chemokines in vitro (5334). Moreover, proinflammatory cytokines and chemokines are present in situ in lupus GN and other inflammatory renal diseases (53,55,56). Together with our findings, these data suggest the possibility that CD40L+ mononuclear cells interact with CD40+ renal target cells and induce or enhance production of proinflammatory molecules.…”
Section: Discussionsupporting
confidence: 84%
“…Renal tubule cells are competent to produce proinflammatory cytokines and chemokines in vitro (5334). Moreover, proinflammatory cytokines and chemokines are present in situ in lupus GN and other inflammatory renal diseases (53,55,56). Together with our findings, these data suggest the possibility that CD40L+ mononuclear cells interact with CD40+ renal target cells and induce or enhance production of proinflammatory molecules.…”
Section: Discussionsupporting
confidence: 84%
“…The direct regulation of IL-6 by JunB emphasizes IL-6 as a target for anti-cytokine therapy in human SLE patients. IL-6 has been suggested to play a role in the development of SLE (21), and especially in patients with Lupus-nephritis, IL-6 levels are significantly increased (29,30). In addition it was shown that IL-6 can experimentally deteriorate lupus nephritis (7) and that IL-6R blockage can improve it (31).…”
Section: Discussionmentioning
confidence: 99%
“…Except for the early stage (Day 3), which might reflect deposition of systemic IL-6, most of the glomerular/cortical IL-6 overexpression appeared to derive from intraglomerular cells other than podocytes and, may at least in part reflect monocyte/macrophage-or mesangial cell sources. 2,5,31 While late restitution of circulating sgp130 in NTN may have antagonized IL-6 trans-signaling, intracellular regulators of IL-6R-gp130 signaling (e.g., SOCS3) were also upregulated in nephritic kidneys and likely counteracted prolonged activation by IL-6. Our second major finding was that pan-IL-6 inhibition, initiated after the early IL-6 peak, i.e., in a therapeutic fashion, had no detectable effect on the course of NTN.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] It is mostly produced by leukocytes but can also be secreted from glomerular endothelial and mesangial cells upon stimulation with, for example, angiotensin II and by podocytes following endotoxin administration in vivo. [6][7][8] However, the role of IL-6 signaling in glomerular disease, in particular in rapidly progressive glomerulonephritis (RPGN), remains controversial.…”
mentioning
confidence: 99%